Pictorial key to the fourth-instar larvae of the subgenera and species of Culex (Diptera: Culicidae) known to occur in Iran - Azari-Hamidian, Shahyad (Zootaxa, 2025)
Pictorial key are provided for the identification of the fourth-instar larvae of the five subgenera and 19 species of Culex Linnaeus, 1758 (Diptera: Culicidae) known to occur in Iran. Some notes are added to aid identification of the species.